A novel device for measuring the ultrasonic wave velocity and the thickness of hyperelastic materials under quasi-static deformations. (April 2019) - Lo Savio, Fabio; Bonfanti, Marco
Abstract: An innovative low-cost testing machine for measuring simultaneously the ultrasonic longitudinal wave velocity and the thickness of hyperelastic material specimens, while applying a quasi-static deformation, is described. In a pulse-echo ultrasonic immersion test, both of these parameters can be obtained by measuring several times of flight, once the speed of sound in the coupling fluid at the testing temperature is known. The variation in ultrasonic longitudinal wave velocity through the sample when the deformation changes is called the acoustoelastic effect. Knowledge of this effect allows the material characterization. The results obtained on SBR-1502 reinforced with carbon black (20%) are in accordance to the values presented in literature and thus confirm the validity of the proposed experimental device. Highlights: The machine presented is able to makes both measurements of ultrasonic wave velocity and hyperelastic material thicknesses. A load application system, operating immersed in the coupling medium, allow to perform the ultrasonic immersion technique. A post-processing system, based on an optimized cross-correlation method, allowed to reach a high accuracy level. The proposed device was validated on SBR-1502 filled with 20% nano-particles of carbon black.